Synopsis of the bee genus Thygater Holmberg 1884 (Hymenoptera, Apidae) in the Brazilian state of Minas Gerais, with the description of a new species and a key to all Brazilian species - Freitas, Felipe V.; Silveira, Fernando A. (Zootaxa, 2017)
Thygater Holmberg 1884, a Neotropical bee genus distributed from Argentina to Mexico, was last revised almost 50 years ago. Considering the species recognized then, and a few others described subsequently, 30 species are currently included in the genus. The Brazilian state of Minas Gerais is a large, environmentally heterogeneous territory, including areas in the phytogeographic domains of the Atlantic Tropical Rain Forest, the semiarid Caatinga and the highly seasonal Cerrado. The state insect fauna has been poorly sampled and studied. As part of a taxonomic and phylogenetic study of the genus, a synopsis of Thygater occurring in the state of Minas Gerais was produced, including the description of a new species (Thygater danunciae Freitas & Silveira, sp. n.), the recognition of two new synonymies, and an identification key for all 15 species of Thygater recorded for Brazil.